2021
DOI: 10.31557/apjcb.2021.6.2.161-169
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Cytomegalovirus in Breast Cancer: A Systematic Review

Abstract: Background: Breast cancer is the most common malignancy among women around the world, with several risk factors contributing to its progression. The role of infectious agents such as viruses in the progression of this cancer is relatively well-known, as a result of various studies in different geographical regions that reported the prevalence of cytomegalovirus in breast cancer. Objective: In this systematic review, we tried to examine the prevalence of cytomegalovirus in breast cancer. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…In the MENA region six studies were found: three in Iran, two in Egypt, and one in Iraq. In these studies, CMV was detected in 6.3-54% of the BC tissue compared to 0-28% in controls [41][42][43][44][45]. In our study, CMV was detected in 13.6% of the patients, which aligns with previous studies [42][43][44]46].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the MENA region six studies were found: three in Iran, two in Egypt, and one in Iraq. In these studies, CMV was detected in 6.3-54% of the BC tissue compared to 0-28% in controls [41][42][43][44][45]. In our study, CMV was detected in 13.6% of the patients, which aligns with previous studies [42][43][44]46].…”
Section: Discussionsupporting
confidence: 91%
“…In these studies, CMV was detected in 6.3-54% of the BC tissue compared to 0-28% in controls [41][42][43][44][45]. In our study, CMV was detected in 13.6% of the patients, which aligns with previous studies [42][43][44]46]. It is noteworthy that a New Zealand study revealed that CMV was completely absent in BC tissue samples from New Zealand women [47], while a study in China has shown that all BC cases were positive for CMV [48].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of cell line studies also showed that CMV infection could play a role in breast cancer (6). Overall, the high prevalence of viruses in breast cancer compared to normal samples indicates the role of viruses in the spread of breast cancer (7).…”
Section: Introductionmentioning
confidence: 89%